Acupuncture versus cognitive behavioral therapy for pain among cancer survivors with insomnia: an exploratory analysis of a randomized clinical trial - Mingxiao Yang (Nature Portfolio, 2021)
Abstract Pain and insomnia often co-occur and impair the quality of life in cancer survivors. This study evaluated the effect of acupuncture versus cognitive behavioral therapy for insomnia (CBT-I) on pain severity among cancer survivors with comorbid pain and insomnia. Using data from the CHOICE trial that compared acupuncture versus CBT-I for insomnia among cancer survivors, we analyzed the effect of interventions on pain outcomes in 70 patients with moderate to severe baseline pain. Interventions were delivered over eight weeks. We assessed average pain severity (primary outcome) and pain interference at baseline, week 8, and week 20. We further defined insomnia and pain responders as patients who achieved clinically meaningful improvement in insomnia and pain outcomes, respectively, at week 8. We found that compared with baseline, the between-group difference (-1.0, 95% CI -1.8 to -0.2) was statistically significant favoring acupuncture for reduced pain severity at week 8 (-1.4, 95% CI -2.0 to -0.8) relative to CBT-I (-0.4, 95% CI-1.0 to 0.2). Responder analysis showed that 1) with acupuncture, insomnia responders reported significantly greater pain reduction from baseline to week 4, compared with insomnia non-responders (-1.5, 95% CI -2.7 to -0.3); 2) with CBT-I, pain responders reported significantly greater insomnia reduction at week 8, compared with pain non-responders (-4.7, 95% CI -8.7 to -1.0). These findings suggest that among cancer survivors with comorbid pain and insomnia, acupuncture led to rapid pain reductions, which contributed to a decrease in insomnia, whereas CBT-I had a delayed effect on pain, possibly achieved by insomnia improvement.